SELECTING OF YOUNG SWIMMERS BASED ON ANTHROPOMETRIC AND MORPHOFUNCTIONAL INDICATORS - Matnazarov Khayrulla Yuldashovich (Sciental Journals Publishing, 2025)
The article provides recommendations for predicting the sports results of young swimmers based on their morphofunctional indicators and for optimizing the training process. The primary focus is directed towards classifying the factors that determine the effectiveness of selection, developing a model for selection based on anthropometric indicators, studying the influence of swimmers' body length in relation to standard biological development on sports results, and creating criteria aimed at improving the efficiency of selection.
Keywords: Swimming, young swimmers, selection, selection criteria, morphofunctional indicators, anthropometric indicators, standard biological development, physical development.